2013
DOI: 10.1007/978-3-319-02493-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Design for Safety: A New Service for Alarming and Informing the Population in Case of Emergency

Abstract: Abstract. In case of emergencies the population in danger should

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The content of warning given to inhabitants was important to their definition of risk warning information. According to Jagtman, the degree to which the warning is understood depends on text features such as length and structure [48]. Ash et al noted that real-time reporting with graphical information is particularly useful [49].…”
Section: Risk Warning Informationmentioning
confidence: 99%
“…The content of warning given to inhabitants was important to their definition of risk warning information. According to Jagtman, the degree to which the warning is understood depends on text features such as length and structure [48]. Ash et al noted that real-time reporting with graphical information is particularly useful [49].…”
Section: Risk Warning Informationmentioning
confidence: 99%
“…Samarajiva and Waidyanatha [55] evaluated mobile technologies in Sri Lanka and they concluded that disaster risk reduction could be improved using mobile application and used to leverage the explosive diffusion of the technology even among the poor in developing countries. Jagtman [56] also evaluated the challenges and opportunities of using cell phones as part of early warning systems in the Netherlands. However, not all researchers have concluded that the use of cell phones is the most cost-effective means of disseminating disaster warning information.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency broadcasting message can be transported by varies of ways, such as mobile network [1,2], Internet network [3], FM network [4], digital TV network [5] and so on. In the article, we pay our focus on researching emergency transportation scheme for rural areas in China.…”
Section: Introductionmentioning
confidence: 99%